ENGGUNAAN INPUT PRODUKSI DAN PRODUKTIVITAS RUMPUT LAUT Gracillaria sp DI PROVINSI SULAWESI SELATAN: THE USE OF PRODUCTION INPUTS AND PRODUCTIVITY OF SEAWEED Gracillaria sp IN SOUTH SULAWESI PROVINCE - Nur Alam Kasim; Megawati Megawati; Nurjannah Bando (Jurnal Agribis, 2019)
The era of market globalization and investment liberalization has made the role of the fisheries sector increasingly important and strategic as a mainstay for economic growth. Seaweed (Gracillaria sp) is one of the strategic commodities in the revitalization program of the fisheries sector. The production during the period of 2007-2011 was increased by an average of 10.09 - 84.18%, but still having production fluctuations every year. This research aims to analyze the inputs that affect the production and productivity of Gracillaria sp seaweed in the province of South Sulawesi. The type of data used is primary and secondary data. Regional samples were determined by multistage cluster sampling while farmer samples were determined by proportional random sampling. The analytical methods used are descriptive analysis and multiple linear regression analysis with the Cobb-Douglas production function model. The results showed that Gracillaria sp seaweed production inputs were: seedlings, urea fertilizer, phonska fertilizer, pesticides, and labor. Its productivity is positively influenced by the variables of seedlings, urea fertilizer, phonska fertilizer, and labor, while the land area variable has a negative effect.